Association between body composition, survival, and toxicity in advanced esophagogastric cancer patients receiving palliative chemotherapy. Issue 1 (21st January 2019) - Dijksterhuis, Willemieke P.M.; Pruijt, Maarten J.; van der Woude, Stephanie O.; Klaassen, Remy; Kurk, Sophie A.; van Oijen, Martijn G.H.; van Laarhoven, Hanneke W.M.
Abstract: Background: Palliative systemic treatment in patients with advanced or metastatic esophagogastric cancer may result in improved overall survival and quality of life but can also lead to considerable toxicity. In various cancer types, severe muscle mass depletion (sarcopenia) and poor muscle strength are associated with decreased survival and increased chemotherapy‐related toxicity. The aim of this study is to determine the impact of body composition on survival and chemotherapy toxicity in esophagogastric cancer patients treated with first‐line palliative chemotherapy. Methods: A total of 88 patients with advanced esophagogastric cancer treated with standard first‐line palliative systemic therapy consisting of capecitabine and oxaliplatin (CapOx) between January 2010 and February 2017 were included. Skeletal muscle index (SMI), reflecting muscle mass, and skeletal muscle density (SMD), associated with muscle strength, were measured using pre‐treatment of all patients and evaluation computed tomography scans after three treatment cycles of 65 patients and were used to determine sarcopenia and sarcopenic obesity (i.e. sarcopenia and body mass index >25 kg/m 2 ). The associations between body composition (SMI, SMD, sarcopenia, and sarcopenic obesity) and survival and toxicity were assessed using univariable and multivariable Cox and logistic regression analyses, respectively. Results: Of 88 patients, 75% was male, and median age was 63 (interquartile range 56–69) years. The majority of patients had an adenocarcinoma (83%). Before start of treatment, 49% of the patients were sarcopenic, and 20% had sarcopenic obesity. Low SMD was observed in 50% of patients. During three cycles CapOx, SMI significantly decreased, with a median decrease of 4% (interquartile range −8.6–−0.4). Median progression‐free and overall survival were 6.9 and 10.1 months. SMI, SMD, sarcopenia, and sarcopenic obesity (both pre‐treatment and after three cycles) were neither associated with progression‐free nor overall survival. Pre‐treatment SMD was independently associated with grade 3–4 toxicity (odds ratio 0.94; 95% confidence interval 0.89–1.00) and sarcopenic obesity with grade 2–4 neuropathy (odds ratio 3.82; 95% confidence interval 1.20–12.18). Conclusions: Sarcopenia was not associated with survival or treatment‐related toxicity in advanced esophagogastric cancer patients treated with CapOx. Pre‐treatment sarcopenic obesity was independently associated with the occurrence of grade 2–4 neurotoxicity and skeletal muscle density with grade 3–4 toxicity.